Experimental characterization of thermal, mechanical, physical and morphological performance of thermoplastic polyurethane composites containing acidic pumice - Ümit Tayfun; Ahmet Bulut; Mehmet Yurderi (MANAS: Journal of Engineering, 2025)
Pumice powder, with its porous structure and low density, is a metal support material in water purification, catalysis manufacturing, and light construction materials. Acidic pumice has a significant proportion of silica. In this study, it was aimed to increase the mechanical and physical performances, as well as the reduction in the specific gravity and cost values, with the addition of acidic pumice to the thermoplastic polyurethane (TPU) polymer, which is used in various sectors such as textile, logistics, construction, and medical applications. Acidic pumice powder was blended with TPU at 2.5, 5.0, 7.5, and 10.0 weight percentages via the melt blending technique for this aim. In addition to mechanical testing such as tensile and hardness, thermal gravimetric analysis, melt flow rate, and electron microscopy (SEM) characterization methods were used on injection-molded composite samples. The structure of the pumice powder was studied using SEM/energy diffraction X-rays. Results revealed that the inclusion of pumice reduces the tensile strength and percent elongation values of TPU, but the composite sample with 2.5% pumice produced virtually equal values to the reference polymer. The hardness of the pumice increased with the loading rate. The low percentage of pumice reinforcement improved TPU's thermal stability. The melt flow rate produced varying results at different pumice ratios. As the morphological qualities were studied using electron microscopy, it was determined that the pumice particles were homogeneously disseminated in the TPU phase when reinforced at 2.5% and 5.0%. Based on these findings, TPU-based composites with the lowest addition quantity of 2.5% pumice produced the best outcomes. The use of pumice-filled TPU composites in automotive and construction applications can be established effectively thanks to performance improvement in the properties of examined samples.